RESPONSIVE LOAD MODEL INTEGRATION WITH SCUC TO DESIGN TIME-OF-USE PROGRAM - Samimi, Abouzar (Institute of Advanced Engineering and Science)
Appropriate designing and accurate pricing of demand response (DR) programs are two important issues being encountered by system operator. Assigning proper values could impact on creating more incentives and raising customers? participation level as well as improving technical and economical characteristics of the power system.Here, time of use (TOU) as a prevalent program is linearly modeled based on concepts of self and cross price elasticities of demand. In order to design TOU program, a joint optimization over the operation cost and customers? benefit is proposed based on security-constrained unit commitment problem (SCUC). Supplementary constraints are provided at each load point with daily energy consumption requirement and DR limitation. GAMS software is used to implement the proposed method in which CPLEX solver finds the optimal solution.IEEE 24-bus test system is employed to study different features of the proposed method. By varying DR potential in the system, TOU rates are determined and then their impacts on customers' electricity bill, operation cost, and reserve cost as well as load profile of the system are investigated. In addition, the effect of network congestion as a technical limitation is studied. The results show the effectiveness and applicability of the proposed method.